Explore BrainMass

# Gradient, Divergence and Curl (II)

Not what you're looking for? Search our solutions OR ask your own Custom question.

This content was COPIED from BrainMass.com - View the original, and get the already-completed solution here!

Real Analysis

Verify
1.&#9660;*(F × G) =G*&#9660;×F - F*&#9660;×G
2.&#9660;×(fF) = f&#9660;×F + (&#9660;f)×F

If (&#9660;^2 = &#948;^2/&#948;x^2 + &#948;^2/&#948;y^2 + &#948;^2/&#948;z^2)
Show
3. &#9660;*(f&#9660;g - g&#9660;f) = f&#9660;^2g - g&#9660;^2f

#### Solution Summary

This solution is comprised of a detailed explanation of the problems of Gradient, Divergence and Curl.
It contains step-by-step explanation for the following problem:
Verify
1.&#9660;*(F × G) =G*&#9660;×F - F*&#9660;×G
2.&#9660;×(fF) = f&#9660;×F + (&#9660;f)×F

If (&#9660;^2 = &#948;^2/&#948;x^2 + &#948;^2/&#948;y^2 + &#948;^2/&#948;z^2)
Show
3. &#9660;*(f&#9660;g - g&#9660;f) = f&#9660;^2g - g&#9660;^2f

Solution contains detailed step-by-step explanation.

\$2.49